Jointed rock failure mechanism: a method of heterogeneous grid generation for DDARF - Ma, Hai Ping; Nik Daud, Nik Norsyahariati (Multidisciplinary Digital Publishing Institute, 2022)
The original DDARF (discontinuous deformation analysis for rock failure) can only generate uniform grids, and the increase in the number of grids reduces the efficiency of calculation, which limits the use of DDARF in large-scale geotechnical engineering. This is a problem that needs to be solved in the original DDARF. A new method is proposed in this paper to optimize the generation of grids in DDARF, and the optimized DDARF can generate heterogeneous grids. The model of the Brazilian disc-splitting experiment was established by using the optimized DDARF, fine grids were generated in the crack propagation region of the model, andsparse grids were generated at the edge of the model. The simulation results show that the Brazilian disc-splitting experiment simulated by the optimized DDARF is more consistent with the physical experiment than the original DDARF. The optimized DDARF and the original DDARF were used to generate a heterogeneous grid model and a uniform grid model, respectively, to simulate the uniaxial compression experiment. Through the analysis of the experimental results, it can be concluded that the optimized DDARF is more accurate in simulating the cracking and propagation of joints in rock blocks, the results of optimized DDARF are more consistent with the simulation results of other software, and the computational efficiency of the optimized DDARF simulation experiment is much higher than that of the original DDARF at the same time.